2004
DOI: 10.1016/j.ijms.2003.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric and laser spectroscopic characterization of a supersonic planar plasma expansion

Abstract: A mass spectrometric and laser spectroscopic experiment has been performed to characterize reactive species that are formed in a supersonic planar plasma expansion generated by discharging a high-pressure gas pulse in a multi-layer slit nozzle geometry. Discharges through mixtures of nitrogen, water and acetylene in He have been studied. The mass spectrometric study uses a state-of-the-art time-of-flight setup. Besides (cluster) cations, with sizes as large as (H 2 O) 56 H + , a variety of pure carbon chain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
(42 reference statements)
0
11
0
1
Order By: Relevance
“…Although we were expecting a rather congested spectrum, reflecting the many compounds that may be formed in the plasma expansion (Witkowicz et al 2004) and likely present in the outflows of the Red Rectangle, we only recorded a limited set of rotationally resolved bands. In Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we were expecting a rather congested spectrum, reflecting the many compounds that may be formed in the plasma expansion (Witkowicz et al 2004) and likely present in the outflows of the Red Rectangle, we only recorded a limited set of rotationally resolved bands. In Figs.…”
Section: Resultsmentioning
confidence: 99%
“…discharge cells) with a number of disadvantages, such as spectral congestion and a lower detection sensitivity because of a lower state density. Comparable plasma sources have shown to generate a large sample of hydrocarbon radicals of the form C n H m ± Witkowicz et al 2004). In direct absorption rotational spectra of molecules like C 6 H or HC 6 H + (Pfluger et al 1999) have been observed.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of cluster ions using the molecular beam apparatus in our laboratory has previously been described in detail [6,7,14,15]. Briefly, Ti x O + y clusters are produced in a first vacuum chamber where a rotating titanium target is placed just in front of an oxygen (O 2 ) gas pulsed nozzle (5 bar backing pressure) and is irradiated by a pulsed laser (Nd:YAG second harmonic at 532 nm, 6 ns pulse width, 10 Hz repetition rate, 1 J/cm 2 fluence).…”
Section: Methodsmentioning
confidence: 99%
“…It is used in the present study in Amsterdam (see also Ref. [16]). More specifically the present experiment comprises a 3 cm  100 lm slit nozzle consisting of two metal jaws that act as cathode and a slotted metal anode, separated by a slotted ceramic plate.…”
Section: Methodsmentioning
confidence: 99%